2021
DOI: 10.1088/1757-899x/1047/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and practical application of autocorrelation functions of vibroacoustic oscillations in a machine dynamic system

Abstract: The paper considers applying the residue theory in obtaining mathematical models for autocorrelation functions of vibroacoustic oscillations in a machine dynamic system during the cutting process. It shows that these models are analogous to experimental data and reflects their practical application for assessing the dynamic quality of machine tools and setting a processing mode. Calculating the dynamic system stability margin is carried out automatically according to the oscillation index obtained from a real … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In the article [7], the authors concluded, that by registering vibroacoustic vibrations during cutting, one could then calculate the autocorrelation function, and then, after performing the appropriate mathematical processing according to the methods of the theory of automatic control, form the corresponding estimates correlated with the dynamic state of the technological system. The article [8] is devoted to obtaining a simple expression for determining the transfer function of a closed dynamic system of a lathe by an experimental and analytical method. The transfer function can be calculated if an analytical expression for the autocorrelation function of the output signal is obtained, for example, by identification by the experimentally recorded vibroacoustic vibrations of the cutter of a lathe.…”
Section: State-of-the-art In Modern Mechanical Engineeringmentioning
confidence: 99%
“…In the article [7], the authors concluded, that by registering vibroacoustic vibrations during cutting, one could then calculate the autocorrelation function, and then, after performing the appropriate mathematical processing according to the methods of the theory of automatic control, form the corresponding estimates correlated with the dynamic state of the technological system. The article [8] is devoted to obtaining a simple expression for determining the transfer function of a closed dynamic system of a lathe by an experimental and analytical method. The transfer function can be calculated if an analytical expression for the autocorrelation function of the output signal is obtained, for example, by identification by the experimentally recorded vibroacoustic vibrations of the cutter of a lathe.…”
Section: State-of-the-art In Modern Mechanical Engineeringmentioning
confidence: 99%